Morpho-Physical and Psycho-Social Determinants of Low Back Pain in Midwives Population in Benin.... - ALAGNIDE, HOUNTONDJI ETIENNE; NIAMA NATTA, D; AZANMASSO, H.; HOUNGBEDJI, M. GERMAIN; DOSSA, ERIC; KPADONOU GODONOU, TOUSSAINT (My University, 2017)
Abstract Background: Low back pain is a real public health problem. Lots of studies have been done about it, but not in midwives group. The latter seem to be exposed to low back pain due to morphological, physical and psycho-social factors. We therefore study the place of these factors in the occurrence of low back pain in midwives. Method: Prospective, cross-sectional and analytical study, it is done with 102 midwives of university hospitals in Benin. They were interviewed and examined. An eventual link with their history of low back pain, for at least 3 months during the last 12 months before the study, was checked to their morphological aspects (spinal curvatures, BMI), physical examinations data (strength and muscular flexibility) and psycho-social factors (relationship with colleagues and either, stress, ...). The effect of these factors was assessed using relative risk (RR) with a 95% confidence interval. Results: Different morpho-physical and psychosocial disturbances were observed in midwives. 81% had a history of low back pain. The latter have a statistically significant relationship with the different factors studied. These were mostly exposure factors, but poor midwife relationship with their hierarchical superiors was a protective factor (RR = 0.69 and p = 0.0106). Discussion- Conclusion: In Benin, health workers and especially midwives are very exposed to low back pain. The latter are often associated with different morphological, physical and psycho-social disturbances. The knowledge of those parameters is interesting to reduce this high prevalence of low back pain in midwives.
Keywords: Low Back Pain; Midwives; Nursing Staff; Psychosocial Disorders